2012
DOI: 10.1371/journal.ppat.1002770
|View full text |Cite|
|
Sign up to set email alerts
|

Opposing Regulation of PROX1 by Interleukin-3 Receptor and NOTCH Directs Differential Host Cell Fate Reprogramming by Kaposi Sarcoma Herpes Virus

Abstract: Lymphatic endothelial cells (LECs) are differentiated from blood vascular endothelial cells (BECs) during embryogenesis and this physiological cell fate specification is controlled by PROX1, the master regulator for lymphatic development. When Kaposi sarcoma herpes virus (KSHV) infects host cells, it activates the otherwise silenced embryonic endothelial differentiation program and reprograms their cell fates. Interestingly, previous studies demonstrated that KSHV drives BECs to acquire a partial lymphatic phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 54 publications
2
21
0
Order By: Relevance
“…Kaposi sarcoma herpes viruses (KSHV) [39] as well as human T cell lymphotropic virus-I (HTLV-I) activate STAT-5 during viral infections [40], while human immunodeficiency viruses (HIV) [41] suppress STAT-5 activity. Interestingly, these viruses also modulate the ATM DNA damage response but a linkage between the two pathways in these viral systems has not been described.…”
Section: Discussionmentioning
confidence: 99%
“…Kaposi sarcoma herpes viruses (KSHV) [39] as well as human T cell lymphotropic virus-I (HTLV-I) activate STAT-5 during viral infections [40], while human immunodeficiency viruses (HIV) [41] suppress STAT-5 activity. Interestingly, these viruses also modulate the ATM DNA damage response but a linkage between the two pathways in these viral systems has not been described.…”
Section: Discussionmentioning
confidence: 99%
“…We also used the SABiosciences' proprietary database (DECODE, DECipherment Of DNA Elements) to search for binding sites of STAT6 in the promoter of the prox-1 gene and discovered that both human and mouse prox-1 genes contain a binding motif for STAT6 in their promoter regions. Furthermore, our group recently reported that STAT5 regulates Prox-1 expression by directly binding to the prox-1 promoter 41 . Thus, it is plausible that STAT6 could also be a transcriptional regulator of Prox-1.…”
Section: Articlementioning
confidence: 98%
“…31 In doing so, apoA-I sustained lymphatic neovascularization in the presence of TNF. The present results are consistent with preincubation of LECs with apoA-I before TNF treatment reducing total TNF-R1 expression, including the receptor molecules at the cell surface, which confer cellular sensitivity to TNF, and in the Golgi, which is responsible for replenishing cell surface TNF-R1 levels.…”
Section: Discussionmentioning
confidence: 98%